Tethered NHC Ligands for Stereoselective Alkyne Semihydrogenations - Pape, Felix; Teichert, Johannes F. (Synthesis, 2017)
A copper(I)-catalyzed semihydrogenation of internal alkynes has been developed. A variety of oxygen- and nitrogen-tethered N-heterocyclic carbene (NHC) complexes have been investigated, leading to a highly Z-selective transformation. The catalyst is generated from inexpensive copper(I) chloride in situ and allows catalytic semihydrogenation down to 10 bar H2.
Keywords: alkynes; dihydrogen; copper; stereoselectivity; hydrogenation; NHC ligands